Using Ylide Functionalization to Stabilize Boron Cations. (10th February 2017) - Scherpf, Thorsten; Feichtner, Kai‐Stephan; Gessner, Viktoria H.
Abstract: The metalated ylide YNa [Y=(Ph3 PCSO2 Tol) − ] was employed as X, L‐donor ligand for the preparation of a series of boron cations. Treatment of the bis‐ylide functionalized borane Y2 BH with different trityl salts or B(C6 F5 )3 for hydride abstraction readily results in the formation of the bis‐ylide functionalized boron cation [Y−B−Y] + (2 ). The high donor capacity of the ylide ligands allowed the isolation of the cationic species and its characterization in solution as well as in solid state. DFT calculations demonstrate that the cation is efficiently stabilized through electrostatic effects as well as π‐donation from the ylide ligands, which results in its high stability. Despite the high stability of2 [Y−B−Y] + serves as viable source for the preparation of further borenium cations of type Y2 B + ←LB by addition of Lewis bases such as amines and amides. Primary and secondary amines react to tris(amino)boranes via N−H activation across the B−C bond.